Efeitos da participação de empreendedoras em Associações de Mulheres de Negócios no estado do Paraná - Balan-Leal, Larissa Estela Berehulka (2011)
Social networks are an important means of development for entrepreneurs and their companies. The training and the insertion into networks are strategies used by entrepreneurs as alternatives to overcoming obstacles and obtaining resources. The objective of this work, aims to know the effects of participation in accordance with the vision of entrepreneurs in women's associations of business in the state of Parana. For both, used-as methodology the qualitative method, performing 26 semistructured interviews with entrepreneurs participants of the Executive Board of the woman entrepreneur in the cities of Curitiba, Ponta Grossa, Foz do Iguaçu, Londrina, Maringá e Campo Mourão and which have occupied or holding the office of President of the respective Councils. The data analysis occurred by the use of the softwares Lexicon 3 and Nvivo 8 resulting in the interpretation of data by means of an analysis léxica and an analysis of content, which resulted in seven categories of analysis. The results showed reasons for the entry in the association and the effects of participation in terms of contributions for companies, as the increase in sales, joint actions, access to credit, training of leaders and the formation of groups of support and organs of support. Also found results-oriented to women entrepreneurs in terms of enlargement of the roles, contacts and knowledge, as well as the identification of barriers to participation and still enlarging the links and relationship with other networks.